Blood-brain barrier breakdown in brain ischemia: Insights from MRI perfusion imaging - Sarvin Sasannia; Richard Leigh; Pouya B. Bastani; Hyeong-Geol Shin; Peter van Zijl; Linda Knutsson; Paul Nyquist (Neurotherapeutics)
Brain ischemia is a major cause of neurological dysfunction and mortality worldwide. It occurs not only acutely, such as in acute ischemic stroke (AIS), but also in chronic conditions like cerebral small vessel disease (cSVD). Any other conditions resulting in brain hypoperfusion can also lead to ischemia. Ischemic events can cause blood-brain barrier (BBB) disruption and, ultimately, white matter alterations, contributing to neurological deficits and long-term functional impairments. Hence, understanding the mechanisms of BBB breakdown and white matter injury across various ischemic conditions is critical for developing effective interventions and improving patient outcomes. This review discusses the proposed mechanisms of ischemia-related BBB breakdown. Moreover, magnetic resonance imaging (MRI) based perfusion-weighted imaging (PWI) techniques sensitive to BBB permeability changes are described, including dynamic contrast-enhanced (DCE-MRI) and dynamic susceptibility contrast MRI (DSC-MRI), two perfusion-weighted imaging (PWI). These PWI techniques provide valuable insights that improve our understanding of the complex early pathophysiology of brain ischemia, which can lead to better assessment and management. Finally, in this review, we explore the implications of the mentioned neuroimaging findings, which emphasize the potential of neuroimaging biomarkers to guide personalized treatment and inform novel neuroprotective strategies. This review highlights the importance of investigating BBB changes in brain ischemia and the critical role of advanced neuroimaging in improving patient care and advancing stroke research.